Adolescents, Stigma, and Social Resistance: A Sociological Study of Self-Harm Behavior in Mataram City - Izzati, Adilah Julia Suma; Wijayanti, Ika; Hakim, Latifa Dinar (Universitas Pattimura, 2025)
The phenomenon of self-harm among adolescents is an increasingly urgent social issue that requires in-depth investigation. This study aims to understand how self-harming behaviors are socially constructed, and how stigma and forms of social resistance emerge and are interpreted by those who engage in them. Conducted in the city of Mataram, this qualitative research employed in-depth interviews, participant observation, and document analysis as secondary data sources. The findings reveal that self-harm is not merely an expression of individual pathology, but rather a response to social pressures, structural inequalities, and cultural expectations that burden adolescents. Social stigma reinforces marginalization and deepens the sense of isolation experienced by individuals. Nevertheless, these conditions also give rise to forms of social resistance, such as peer support and solidarity within small communities. This study highlights the importance of a sociological approach to uncover the social dimensions of adolescent mental health issues. The novelty of this research lies in its revelation of self-harm as a symbolic battleground between social pressure and the search for self-meaning. It recommends the development of more inclusive and responsive social policies while contributing to a more empathetic and transformative social science and humanities discourse.